Research on the Construction of the Organizational Mechanism of Rural Party Branches - Chen, Hui (International Journal of Social Sciences and Public Administration, 2024)
Xi Jinping stressed that party members and cadres must be politically strong and strong, and the party organization must have superb leadership ability to provide a strong political guarantee for the implementation of the rural revitalization strategy. The problems in the organizational construction of rural party branches are mainly manifested in the imperfect selection mechanism of branch members, the loss of a large number of outstanding local talents, and the weak economic awareness of rural party members. Therefore, how to build a complete organizational mechanism of rural party branches around the three aspects is the core of improving the leadership ability of rural party branches, and it is also the key to giving full play to the leadership of rural party branches to lead the people to achieve rural revitalization.